Role of β-Interferon Inducer (DEAE-Dextran) in Tumorigenesis by VEGF and NOTCH1 Inhibition along with Apoptosis Induction - Bakrania, Anita K.; Variya, Bhavesh C.; Patel, Snehal S. (Frontiers in Pharmacology, 2017)
As a novel target for breast cancer, interferon inducers have found its role as anti-angiogenic agents with DEAE-Dextran being a molecule used for centuries as a transfection agent. Our results herein offer an explanation for the emergence of DEAE-Dextran as an anti-tumor agent for TNBC with in-depth mechanistic approach as an anti-angiogenic molecule. DEAE-Dextran has found to possess cytotoxic activity demonstrated during the various in vitro cytotoxicity assays; moreover, as an anti-oxidant, DEAE-Dextran has shown to possess excellent ROS scavenging activity. The interferon inducing capacity of DEAE-Dextran was determined qualitatively as well as quantitatively specifically demonstrating overexpression of β-interferon. As a measure of anti-proliferative activity, DEAE-Dextran exhibited reduced ki67, p53 and PCNA levels. Also, overexpression of CK5/6 and p63 in DEAE-Dextran treated animals indicated improvement in breast cell morphology along with an improvement in cell-cell adhesion by virtue of upregulation of β-catenin and E-cadherin. Anti-angiogenic property of DEAE-Dextran was concluded by the downregulation of CD31, VEGF and NOTCH1 both in vivo and in vitro. Further, apoptosis due to DEAE-Dextran, initially determined by downregulation of Bcl2, was confirmed with flow cytometry. Overall, results are defensive of DEAE-Dextran as an emerging anti-tumor agent with mechanisms pertaining to β-interferon induction with probable VEGF and NOTCH1 inhibition as well as apoptosis which still needs to be studied in further depth.